Compliance with COVID-19 Social-Distancing Measures in Italy: The Role of Expectations and Duration - Guglielmo Briscese; Nicola Lacetera; Mario Macis; Mirco Tonin (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study how intentions to comply with the self-isolation restrictions introduced in Italy to mitigate the COVID-19 epidemic respond to the length of their possible extension. Based on a survey of a representative sample of Italian residents (N=894), we find that respondents who are positively surprised by a given hypothetical extension (i.e. the extension is shorter than what they expected) are more willing to increase their self-isolation. In contrast, negative surprises (extensions longer than expected) are associated with a lower willingness to comply. In a context where individual compliance has collective benefits, but full enforcement is costly and controversial, communication and persuasion have a fundamental role. Our findings provide insights to public authorities on how to announce lockdown measures and manage people's expectations.
Keywords: C42; D91; H12; H41; I12; 330; COVID-19; social distancing; expectations